Pengaruh Tanaman Stylosanthes Guyanensis Terhadap Produksi Beberapa Jenis Rumput Pada Sistem Penanaman Bercampur - M. Yunus (Agricultural Faculty, 2007)
ABSTRACT.A research on the effect of Stylosanthes guyanesis on production of Pannicum maximum, Staria splendid, Brachiaria decumbens, and Cynodon Plectostachyus have been conducted at UPTD (Unit Pelaksana Tugas Dinas) Saree, Aceh Besar. The grasses were planted mixed with stylosanthes guyanesis. The method used was completely randomized design (CRD) with factorial pattern of 4 x 4 with 4 replications. The first factor consist of 4 different kind of grasses e.g Pannicum maximum (R1) Staria splendid (R2), Brachiaria decumbens (R3) and Cynodon Plectostachyus (R4). The second factor was mixed palnting with stylosanthes guyanesis. Parameters studied were number of tiller, height of grass, and herbage yield. Data were analyzed by analyzed of variance and continued by least significant different test (LSD) (Steel and Torrie, 1983). The result showed that mixed cultivation of grass with leguminose (Stylosnthes guyanesis) was better on number tiller, height of grass, and herbage yield compared to unmixed planting grasses.